2004
DOI: 10.1051/0004-6361:20035895
|View full text |Cite
|
Sign up to set email alerts
|

The WEBT BL Lacertae Campaign 2001 and its extension

Abstract: paper we present UBVRI light curves obtained by the WEBT from 1994 to 2002, including the last, extended BL Lac 2001 campaign. A total of about 7500 optical observations performed by 31 telescopes from Japan to Mexico have been collected, to be added to the ∼15 600 observations of the BL Lac Campaign 2000. All these data allow one to follow the source optical emission behaviour with unprecedented detail. The analysis of the colour indices reveals that the flux variability can be interpreted in terms of two com… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
90
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 123 publications
(108 citation statements)
references
References 18 publications
18
90
0
Order By: Relevance
“…The BWB trend has been found to be predominant in BL Lacertae by all optical observations of this source till date during both flaring and steady states (Ghosh et al 2000;Gu et al 2006) which was revealed by our observations also. Villata et al (2004b) found that the intraday flares followed BWB trend strongly with a slope of ∼ 0.4 which is also the case for our data with the slopes of the intra-night LCs more than ∼ 0.4 in majority of cases. Thus, our colour variability results for the source being strongly chromatic between Oct -Nov 2014 were consistent with those of Villata et al (2004b).…”
Section: Colour-magnitude Relationshipsupporting
confidence: 89%
See 1 more Smart Citation
“…The BWB trend has been found to be predominant in BL Lacertae by all optical observations of this source till date during both flaring and steady states (Ghosh et al 2000;Gu et al 2006) which was revealed by our observations also. Villata et al (2004b) found that the intraday flares followed BWB trend strongly with a slope of ∼ 0.4 which is also the case for our data with the slopes of the intra-night LCs more than ∼ 0.4 in majority of cases. Thus, our colour variability results for the source being strongly chromatic between Oct -Nov 2014 were consistent with those of Villata et al (2004b).…”
Section: Colour-magnitude Relationshipsupporting
confidence: 89%
“…Villata et al (2004b) found that the intraday flares followed BWB trend strongly with a slope of ∼ 0.4 which is also the case for our data with the slopes of the intra-night LCs more than ∼ 0.4 in majority of cases. Thus, our colour variability results for the source being strongly chromatic between Oct -Nov 2014 were consistent with those of Villata et al (2004b). Since the jet emissions are completely dominating the flux from BL Lacerate objects, this can be explained by the shock-in-jet models elaborated under section 8.…”
Section: Colour-magnitude Relationshipsupporting
confidence: 89%
“…The minimum Doppler factor of 11, corresponding to a maximum angle of about 5.0 • , was reached during the flux minima. The above picture would explain the long/midterm flux variations (see also Villata et al 2002Villata et al , 2004, while the short-term flares (see below) would be due either to perturbations moving downstream in the jet or to a finer geometrical structure, as proposed for BL Lacertae by Larionov et al (2010).…”
Section: Flux Correlationsmentioning
confidence: 86%
“…from minutes to years timescales (e.g. Villata et al 2004;Agarwal & Gupta 2015). From ∼ 15 years of variability observations (June 1971 to January 1985), Webb et al (1988) inferred recurrent variations after every 0.31, 0.60, and 0.88 yr using the Fourier periodogram.…”
Section: Bl Lacertaementioning
confidence: 99%